Penerapan Kurikulum Merdeka pada Mata Pelajaran Pendidikan Pancasila - Indira Rohmawati; Suttrisno Suttrisno (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
The curriculum greatly influences the education system in Indonesia. This is evident from the fact that the education system in Indonesia has experienced various changes since the past, but there is still room for improvement in facing global challenges. Currently, the education system in Indonesia implements education based on the "Freedom of Learning" curriculum introduced by the Minister of Education Nadiem Makarim which shows a commitment to educational reform. In the independent curriculum, there is Pancasila education learning as one of the school's missions. Using Pancasila learning refers to the character education that each individual has, differences in character can cause disputes, divisions, and trigger deviant behavior. Implementation of Citizenship Education learning uses differentiated learning based on Ki Hajar Dewantara's educational philosophy. This implementation refers to learning outcomes in the independent curriculum, namely about local wisdom and character, where this becomes basic learning so that students when they are in society are aware of how to behave and position themselves, especially in loving their homeland. Pancasila values ​​and the application of Citizenship Education learning are contained in the Pancasila principles which include the values ​​of mutual cooperation, honesty, responsibility among friends, the surrounding environment and responsibility for what one does. The values ​​that can be contained in Pancasila contain many religious values ​​(first principle), human values ​​(second principle), unity values ​​(third principle), wisdom values ​​(fourth principle), and finally social values ​​(fifth principle). Pancasila values ​​are the way of life for the Indonesian people to build the character values ​​of Indonesian society.